9x-(6x-8)=

Simple and best practice solution for 9x-(6x-8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-(6x-8)= equation:


Simplifying
9x + -1(6x + -8) = 0

Reorder the terms:
9x + -1(-8 + 6x) = 0
9x + (-8 * -1 + 6x * -1) = 0
9x + (8 + -6x) = 0

Reorder the terms:
8 + 9x + -6x = 0

Combine like terms: 9x + -6x = 3x
8 + 3x = 0

Solving
8 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 3x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 3x = 0 + -8
3x = 0 + -8

Combine like terms: 0 + -8 = -8
3x = -8

Divide each side by '3'.
x = -2.666666667

Simplifying
x = -2.666666667

 

See similar equations:

| A^2-4= | | -6(-3x+9)=-18 | | 2(5+x)=22 | | 2T^3-18T=0 | | 1-9x^2= | | 7x+12=-30 | | 2(2-2x)=-4 | | 7x-x=72 | | -7=8v-3 | | 5x+13x=108 | | 3+7x-2x=3+5x | | -3x-13x=128 | | 2x^2-x-21=0 | | p+3p=16 | | 2=5t+9 | | 8x+4=3x+5 | | 4x+6y=8 | | 7+4m-3=5m+12-2m | | 15x^2-13x+2=0 | | (5x+3)(x^2-x-20)=0 | | Y^2-81= | | 3y-8+y+46=5y+40-3y | | 1x+20=.5x+30 | | a^2-49= | | 5.3x-3.44=4.24-4.3x | | 4x^2+6x=13 | | x^3+5x^2+6x= | | 11x+5=7x+50 | | 4x^2-y^2= | | 90=10(3y+3) | | 4x^2+16xy-9y^2= | | -24+x=x-24 | | 9+4n=15-2n | | 15x^2-x-6= | | 3(t-4)+7t=5(2t+4)-9 | | 3(4x-1)-(3x+2)=4(x-2) | | 8x-(5x+4)=5 | | B^2-9= | | 10x^2-11x-6= | | 2x+y-3=27 | | 20x^3+22x^2+6x=0 | | 24x-7-16x+3=19x-5-11x+17 | | -v^2=-10v+9 | | 15=-7+1 | | x^2+-7+-8=0 | | C^2-16= | | 15=-7v+1 | | 9x^2-36x+36=0 | | 4(2x+8)=2(5x+10) | | 49x^2-16y^4= | | 4w=60 | | 2(x-6)+4=4(x+2)-10 | | 5X^2=32X+12 | | 25-x^2y^2= | | 2x+x-3=27 | | t+5+t-5-13t-65+42=0 | | 22x-8-16x=3(2x-4)+4 | | 2x^2+3x+1=0 | | Y^2-64= | | 9x-6=6y+5 | | 16-18x^2= | | 7=3+17t-16t^2 | | 2x^2+6x-108= | | 4x^2-1= | | 9x-6=7x+22 |